Dendroflora parku zamkowego w Uniejowie – stan obecny i zmiany - Kucharski, Leszek; Chmielecki, Błażej (Biuletyn Uniejowski, 2014)
The castle park in Uniejów was founded between 1860 and 1870. Today it has an area of 32 ha and 151 taxa of trees and shrubs, which consist of 101 native and non-native species of trees andbushes and 50 cultivated varieties. Owing to the natural character of trees found in most of the park area its dendroflora mainly consists of native species, of which Quercus robur, Fraxinus excelsior, Ulmus laevis and Fagus sylvatica stand out because of their size. The most valuable taxa include Gymnocladus dioicus, Juglans nigra, Quercus macranthera, Taxodium distichum ans Platanus x hispanica. In the past there were some tree species which are not found in the park today, such as Corylus colurna, Malus prunifolia, Populus nigra ‘Italica’, or Tilia platyphyllos ‘Laciniata’. In the years 2013−2014, 62 taxa were added to the park dendroflora. They mainly consist of cultivated species of shrubs, mostly colourful varieties of Rhododendron. The revitalisation of the castle park that is now under way is aimed at preservation of its natural landscape, especially in its northern part that is covered by forest.